Cold crucible melting with bottom pouring nozzle. Issue 1 (7th January 2020) - Bojarevics, Valdis; Pericleous, Koulis
Abstract : Purpose: The purpose of this paper is to investigate a new type of nozzle which is free from erosion and non-contaminating the outflow metal. Cold crucible melting technique with electromagnetic induction is used to obtain reactive metal castings and produce high-quality metal powders for aerospace, automotive and medical applications. An important part of this technology is the nozzle used to pour the molten alloy through the bottom opening. Design/methodology/approach: The paper uses mathematical modeling technique, previously validated on multiple similar cases, to investigate a new type of nonconsumable nozzle made of copper segments. Findings: The design of the nozzle requires to satisfy the narrow balance between the thin solidified protective layer on the wall while avoiding the blockage of the outflow if the nozzle is frozen completely. The sensitivity of the outflow to the nozzle diameter is investigated. The AC electromagnetic force leads to high mixing rates, transitional flow structures and turbulence of the melt, contributing to the melt shape dynamics and the heat loss to walls. Originality/value: The beneficial features of the cold crucible melting to purify the melt from particulate contamination are explained using the full melting and pouring cycle.